MOFs for Advanced Applications - Bedia, Jorge; Belver, Carolina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Metal organic frameworks (MOFs) are a class of porous materials with a modular structure. This allows for very wide structural diversity and the possibility of synthesizing materials with tailored properties for advanced applications. Thus, MOF materials are the subject of intense research, with strong relevance to both science and technology. MOFs are formed by the assembly of two components: cluster or metal ion nodes, which are also called secondary building units (SBUs), and organic linkers between the SBUs, usually giving rise to crystalline structures with an open framework and significant porous texture development. The main aim of this Special Issue of Catalysts (ISSN 2073-4344) is to present the most relevant and recent insights in the field of the synthesis and characterization of MOFs and MOF-based materials for advanced applications, including adsorption, gas storage/capture, drug delivery, catalysis, photocatalysis, and/or chemical sensing.